Chelidonine selectively inhibits the growth of gefitinib-resistant non-small cell lung cancer cells through the EGFR-AMPK pathway. (September 2020) - Xie, Ya-Jia; Gao, Wei-Na; Wu, Qi-Biao; Yao, Xiao-Jun; Jiang, Ze-Bo; Wang, Yu-Wei; Wang, Wen-Jun; Li, Wei; Hussain, Shahid; Liu, Liang; Leung, Elaine Lai-Han; Fan, Xing-Xing
Graphical abstract: Highlights: Chelidonine is a novel potential inhibitor of EGFR with L858R/T790M double mutation. Chelidonine significantly represses G–R NSCLC cells growth in vitro and in vivo. Chelidonine-induced apoptosis is associated with mitochondrial damage. Targeting EGFR and inhibition of mitochondrial function to activate the AMPK signaling pathway is a potential anti-cancer therapeutic strategy for G–R NSCLC patients. Abstract: Tyrosine kinase inhibitors (TKIs) have been widely used for the clinical treatment of patients with non-small cell lung cancer (NSCLC) harboring mutations in the EGFR. Unfortunately, due to the secondary mutation in EGFR, eventual drug-resistance is inevitable. Therefore, to overcome the resistance, new agent is urgently required. Chelidonine, extracted from the roots of Chelidonium majus, was proved to effectively suppress the growth of NSCLC cells with EGFR double mutation. Proteomics analysis indicated that mitochondrial respiratory chain was significantly inhibited by chelidonine, and inhibitor of AMPK effectively blocked the apoptosis induced by chelidonine. Molecular dynamics simulations indicated that chelidonine could directly bind to EGFR and showed a much higher binding affinity to EGFR L858R/T790M than EGFR WT, which demonstrated that chelidonine could selectively inhibit the phosphorylation of EGFR in cells with EGFR double-mutation. In vivo study revealed that chelidonine has a similar inhibitory effect like second generation TKI Afatinib. In conclusion, targeting EGFR and inhibition of mitochondrial function is a promising anti-cancer therapeutic strategy for inhibiting NSCLC with EGFR mutation and TKI resistance.